A media monitoring dashboard for university - Su, Jia Sen (2020)
A news media monitoring dashboard benefits university on handling brand reputation by listening to public’s opinion. The automated process of extracting and displaying news article on data dashboard eliminates manually searching for news article to do self update daily. A simple and holistic media monitoring dashboard should become a trend for local universities on taking advantage to compete in the industry. CRISP-DM is the main guide to implement the system. Keywords have to be defined and fine-tuned to extract the most accurate news articles related to local higher education that is useful for target users. News API request for news media sources and returns JSON metadata with details of the updated news. All information collected will be analysed and presented with various visualisation that is useful and simple to understand. Short and precised information of news articles, and the analysis of the data extracted will be display to users as the final product developed by one of the R packages, ShinyDashboard. The main idea is to include artificial intelligence model to accurately categorise data collected, to provide better visualisation in the form of data table and charts.